RESOLUTION OF SYMPTOMATIC IMMOBILIZATION HYPERCALCEMIA (IH) AFTER REHABILITATION EXERCISES IN A HEMODIALYSIS PATIENT - Sun Ae Yoon; Young Ok Kim; Yu Seon Yun (The Korean Society of Nephrology, 2012)
The patient is a 76-year-old Korean female who had been thrice-weekly hemodialysis for 3 months for ESRD attributable to diabetic nephropathy. She presented to emergency room with decreased mentality. Before admission, she had been bed-ridden status for 4 months due to poor general condition. Brain CT and MRI showed negative findings. Serum calcium was 15.6 mg/dl, ionized calcium 2.12 mmol/L, hypercalciuria (FECa 26.2%), and low serum levels of iPTH (42.92 pg/ml) suggested non-parathyroidal hypercalcemia. Two weeks ago, her serum calcium and phosphate level was 9.0 and 6.1 mg/dl, respectively and she was receiving calcium acetate. An extensive workup failed to identify any etiology of hypercalcemia. Hypercalcemia was temporarily ameliorated after withdrawal calcium-containing phosphate binder and daily hemodialysis with low calcium (Ca++ 1.25 mmol/L) dialysate but recurred one week later. Serum calcium level was increased and reached to 12.2-13.5 mg/dl. Immobilization hypercalcemia was considered after the exclusion of other discernible causes. We decided to try rehabilitation exercises. Two weeks after passive range of motion (ROM) exercise of joints and tilting table standing, serum calcium level was decreased to below 10.5 mg/dl.